2021
DOI: 10.3390/ijerph18126285
|View full text |Cite
|
Sign up to set email alerts
|

Population Mobility Trends, Deprivation Index and the Spatio-Temporal Spread of Coronavirus Disease 2019 in Ireland

Abstract: Like most countries worldwide, the coronavirus disease (COVID-19) has adversely affected Ireland. The aim of this study was to (i) investigate the spatio-temporal trend of COVID-19 incidence; (ii) describe mobility trends as measured by aggregated mobile phone records; and (iii) investigate the association between deprivation index, population density and COVID-19 cases while accounting for spatial and temporal correlation. Standardised incidence ratios of cases were calculated and mapped at a high spatial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…Marcos César Ferreira also found that the population most vulnerable to COVID‐19 were those living in the districts with lower salaries and slum areas in the São Paulo municipality, Brazil 19 . Madden et al 22 found a similar result in Ireland; that is, the higher the deprivation index and the larger the population density, the higher the morbidity. However, the stay at home index (an indicator of population mobility) was negatively associated with morbidity.…”
Section: Discussionmentioning
confidence: 90%
“…Marcos César Ferreira also found that the population most vulnerable to COVID‐19 were those living in the districts with lower salaries and slum areas in the São Paulo municipality, Brazil 19 . Madden et al 22 found a similar result in Ireland; that is, the higher the deprivation index and the larger the population density, the higher the morbidity. However, the stay at home index (an indicator of population mobility) was negatively associated with morbidity.…”
Section: Discussionmentioning
confidence: 90%
“…To minimize contact rates and avoid the transmission of COVID-19, it is essential to restrict movement as much as possible (Vannoni et al, 2020). The imposition of lockdown limitations resulted in a significant decrease in human mobility (Madden et al, 2021), Meanwhile, other experts have done comparable mobility studies to ascertain where pet cats travel while they are outdoors. Scientists have attempted to address this subject previously, either by tracking cats on foot or by collaring cats with radio transmitters, but Cat Tracker proved unique in its scope.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, an estimated third of the adult population had experienced some Covid-19 vaccine hesitancy, and 9% were opposed to the vaccine, with trends in resistance steadily increasing as the pandemic progressed [12,13]. As reported internationally, adults in Ireland who are vaccine hesitant are more likely to live-in urban settings and be in a lower income bracket [12], the same areas at increased risk for Covid-19 incidence and comorbidities [9].…”
Section: Introductionmentioning
confidence: 99%
“…SES-related factors such as diminished trust in governmental institutions, poorer health literacy, and logistical di culties simultaneously increase ones' likelihood of being vaccine hesitant [7,8] and ones' vulnerability to Covid-19 if unvaccinated. Experts have called for the prioritisation of densely populated deprived areas during vaccination rollout to capture people at increased risk of infection and hospitalisation [9]. However, ensuring equitable vaccination requires understanding and addressing community-speci c challenges associated with vaccination willingness and uptake [10].…”
Section: Introductionmentioning
confidence: 99%